Pemikiran Politik Al-Ghazālī Seputar Konsesi dan Kontroversi Pengangkatan Kepala Negara - Syamsul Yakin (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2018)
The paper describes an analysis of al-Ghazālī’s political thinking concerning any requirements for the appointment of states kingship which were filled with concessions that caused controversies. The paper reveals the views of experts who claim that Sunni political thought, in which al-Ghazālī’s thought is included, has been characterized by giving legitimacy. By analyzing qualitative data and using historical-critical approach, this paper shows that al-Ghazālī's thought regarding legitimacy by making concessions to the power he defended had made his thoughts were considered as a controversy and arose criticism. However, history proves that al-Ghazālī continued to do that controversy for the continuation of the Abbasid Caliphate which ruled de jure and for the existence of the de facto power of the Saljuk Dynasty who at that time gained political and dogmatic pressure from The Isma’ilis.